Cognitive and Emotional Processes as Predictors of a Successful Transition Into School. Issue 1 (2nd January 2017) - Blankson, A. Nayena; Weaver, Jennifer Miner; Leerkes, Esther M.; O'Brien, Marion; Calkins, Susan D.; Marcovitch, Stuart
ABSTRACT: Research Findings : The aim of this research was to delineate developmental processes that contribute to early school success. To achieve this aim, we examined emotion regulation, executive functioning, emotion knowledge, and metacognition at ages 3 and 4 as distal and proximal predictors of age 5 achievement and school adjustment in a sample of 263 children (42% non-White). We also explored mediational pathways among these 4 processes in the prediction of the age 5 outcomes. Results revealed that all 4 processes affected achievement and school adjustment, but in different ways, with executive functioning emerging as a key predictor. Practice or Policy : Executive functioning was found to be a key factor in predicting achievement and school performance in the kindergarten year. This finding provides support for the development of executive functioning training programs that can be applied in the preschool classroom, particularly for promoting reading development. However, additional emphasis should be placed on both cognitive and emotional processes in the preschool years to promote optimal development.